The Poet of the House of the Living: The memory of leprosy in the literature of Lino Villachá (1933-1994) (TEL Tempo, Espaço e Linguagem, 2023)
Between the years 1946 and 1994, the poet Lino Villachá was an intern in a leprosarium on the Campo Grande/MS, the current hospital-farm São Julião. In these years and inside the asylum-colony, Villachá lived with the isolation practices and various prophylaxes to fight leprosy throughout the second half of the 20th century, where he painted pictures with his poetry, formulating a testimonial account of the conditions of abandonment and misery of those afflicted by the disease. Here we take his work as an analytical basis and a factor of the transformation of the “other” as the author of his own history.